2017
DOI: 10.1332/204674315x14418885009965
|View full text |Cite
|
Sign up to set email alerts
|

Working it out: strategies to reconcile work and family among Swedish lone mothers

Abstract: Drawing on 39 interviews with Swedish lone mothers, this article aims to explore the central coping strategies used by the mothers in reconciling work and family. The article also studies how working conditions and access to economic and social capital influence the coping strategies used. The findings indicate a variety of coping strategies. These were clearly influenced by position in the labour market and access to social and economic capital. While for instance working-class mothers tried to changed jobs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…They also show that the mothers were highly reliant on help from their social networks despite the social services and benefits provided by the state. This finding resonates with research showing that lone mothers across different types of welfare state are dependent on informal care (Alsarve, 2015;Ciabattari, 2007;Gill & Davidson, 2001;Harmann, 2013;Herz & Ferguson, 1997;Kröger, 2010;Nelson, 2006;Millar & Ridge, 2009;Skinner & Finch, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…They also show that the mothers were highly reliant on help from their social networks despite the social services and benefits provided by the state. This finding resonates with research showing that lone mothers across different types of welfare state are dependent on informal care (Alsarve, 2015;Ciabattari, 2007;Gill & Davidson, 2001;Harmann, 2013;Herz & Ferguson, 1997;Kröger, 2010;Nelson, 2006;Millar & Ridge, 2009;Skinner & Finch, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, Baxter and Alexander () found that, in isolation from other factors, Australian single mothers report more WFC than coupled mothers. Single mothers' high levels of WFC may result from having to solely and with limited resources manage responsibilities (Alsarve, ; Roman, ; Son & Bauer, ) that are shared by two individuals in couples. In the absence of a partner, single mothers' total workload—combining work, domestic, and childcare responsibilities—places heavy demands on their family life, particularly compared with two‐parent families, as shown by previous studies from the three countries we examine in the present study (Bakker & Karsten, ; Kinnunen, Malinen, & Laitinen, ; Millar, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas so‐called tag‐team parenting as a childcare‐related strategy can help to reduce coupled mothers' family workload and ensuring that the child receives parental care (see Mills & Täht, ; Murtorinne‐Lahtinen et al, ), single mothers navigate work and family responsibilities without a resident partner. Indeed, qualitative studies conducted in Europe (e.g., Alsarve, ; Roman, ) suggest that nonstandard work hours create major difficulties and pressures, particularly for single mothers in combining work and family life. Thus, we expect that the positive association between the amount of nonstandard work hours and WFC is stronger for single than coupled mothers because nonstandard work hours are unlikely to reduce single mothers' total family‐related workload for which the mother is solely and with more limited resources responsible for, compared with families with two parents (Hypothesis 2b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These relationships can offer for instance emotional and practical support, a support that can be imperative for lone mothers (cf. Alsarve, 2017) because they do not share their everyday life with a (cohabiting) partner. The aim of this paper is thus to contribute to the research on lone mothers by studying their relationships to their friends.…”
Section: Introductionmentioning
confidence: 99%